ANALISIS FAKTOR YANG MEMPENGARUHI AKUNTABILITAS PENGELOLAAN DANA DESA (Studi Kasus Desa Tanjung Gusta, Desa Sunggal Kanan dan Desa Sei Mencirim) - Leni Natalia Siagian; Arthur Simanjuntak; Duma Rachel Situmorang (JURNAL MANAJEMEN, 2022)
This study aims to analyze factors that affect village fund management accountability in Tanjung Gusta Village, Sunggal Kanan Village and Sei Mencirim Village.  The type of research conducted is causal associative research with a quantitative approach.  The sample draw technique uses saturated sampling techniques where all members of the population are used as samples.  In this study, there were 52 people, each of whom was the Tanjung Gusta Village Government of 16 people, the Sunggal Kanan Village Government 13 people and the Sei Mencirim Village Government 23 people from the three villages studied.  The research data was collected by survey. In order to analyze the data, the researchers used SPSS 25 software to find out the multiple linear data of research. The results of this study show that the competence of the apparatus, organizational commitment, and village transparency show a significant positive influence on the accountability of village fund management in Tanjung Gusta Village, Sunggal Kanan and Sei Mencirim.  The utilization of information technology on the other hand, does not affect the accountability of Village Fund Management. Other results showed that all variables were independent as well as had a significant effect on the accountability of village fund management in Tanjung Gusta, Sungal Kanan and Sei Mencirim villages.